2016
DOI: 10.1007/978-1-4939-3387-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SARS Coronavirus Vaccine from Recombinant Spike Protein Plus Delta Inulin Adjuvant

Abstract: Given periodic outbreaks of fatal human infections caused by coronaviruses, development of an optimal coronavirus vaccine platform capable of rapid production is an ongoing priority. This chapter describes the use of an insect cell expression system for rapid production of a recombinant vaccine against severe acute respiratory syndrome coronavirus (SARS). Detailed methods are presented for expression, purification, and release testing of SARS recombinant spike protein antigen, followed by adjuvant formulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…9 Advax is an adjuvant derived from delta inulin, a polysaccharide found in the roots of plants of the Compositae family. 10,11 Advax adjuvant has shown high levels of efficacy in vaccines against respiratory syncytial virus, 11 West Nile virus and Japanese encephalitis virus, 12,13 influenza, [14][15][16] severe acute respiratory syndrome coronavirus, 17 Listeria, 18 onchocercosis 19 and anthrax, 20 amongst others, consistent with its having broad efficacy across viral, bacterial and parasitic vaccines. An advantage of delta inulin adjuvant is that it enhances both Th1 and Th2 T cell responses.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…9 Advax is an adjuvant derived from delta inulin, a polysaccharide found in the roots of plants of the Compositae family. 10,11 Advax adjuvant has shown high levels of efficacy in vaccines against respiratory syncytial virus, 11 West Nile virus and Japanese encephalitis virus, 12,13 influenza, [14][15][16] severe acute respiratory syndrome coronavirus, 17 Listeria, 18 onchocercosis 19 and anthrax, 20 amongst others, consistent with its having broad efficacy across viral, bacterial and parasitic vaccines. An advantage of delta inulin adjuvant is that it enhances both Th1 and Th2 T cell responses.…”
Section: Introductionmentioning
confidence: 84%
“…We have previously shown that Advax delta inulin adjuvant can be combined with other immunomodulators such as TLR9 agonists (CpG oligonucleotides) 17 or NOD2 agonists (murabutide), 20 to make potent combination adjuvants. In this study we hypothesized that a new adjuvant formulation designated as Advax4 that combined all three individual immunomodulatory agents would when combined with rCMX or a new fusion protein of CMX and ESAT-6 (rECMX) induce potent cellular and humoral immune responses that might better control TB infection.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believed that there were four inserts in the S protein of 2019-nCoV, which may be the result of artificial modification. The SARS-S has been widely studied, including vaccine development and drug design[42, 43]. The key residues 663-VSLLRSTSQ-671 involved in SARS-S protein cleavage site was missed in all structures that have been resolved to date due to its flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Studies of SARS-CoV have identified the S1 subunit, especially the RBD of SARS-CoV as a primary target for NAb in mice, NHPs, and humans. 55,[61][62][63][64][65] Similarly, for MERS-CoV, the full-length or fragments of S protein, particularly the RBD, has been used to demonstrate partial efficacy in rhesus macaques 66,67 as well as inducing NAbs in small animal models such as rabbits and mice. 59,60,[68][69][70][71][72][73] A recent study showed that residues 377-588 of MERS-CoV S protein RBD were capable of eliciting potent humoral and cellular responses, which could be enhanced by adding MF59 adjuvant.…”
Section: Protein Subunit Vaccinesmentioning
confidence: 99%